Healthy environments: Understanding perceptions of underrepresented communities in the United Kingdom - Roberts,L; Lounsbury,O; Awuzudike,V; Lawrance,E; Jennings,N (International Journal of Environmental Research and Public Health, 2022)
A healthy environment has been defined by global health organisations as one that is safe, supportive of healthy lifestyles, and free of hazards. Such definitions disregard the complexity of what it means for an environment to be perceived as ‘healthy’—such as the mental, not just physical, health effects on citizens. This study aimed to understand the attributes that underrepresented groups of the United Kingdom (UK) public assign to healthy environments—an important step for directing public policy and actions to create environments that are inclusive of all citizens. This co-created study involved 95 participants from underrepresented communities in 10 separate focus groups, each facilitated by a community member. Thematic analyses highlighted five key attributes of a healthy environment: sounds and sights, accessibility, safety, familiarity and mental health and wellbeing. This study draws a picture of key attributes underrepresented groups of the UK public assign to healthy environments that is richer than that drawn by existing definitions. These findings illustrate the importance of hearing diverse voices when directing research, policy, and actions that attempt to develop healthy environments for all.